Optimal Operating Conditions for Adsorption of Heavy Metals from an Aqueous Solution by an Agriculture Waste - Hummadi, Khalid Khazzal (Iraqi Journal of Chemical and Petroleum Engineering, 2021)
The aim of this work is to detect the best operating conditions that effect on the removal of Cu2+, Zn2+, and Ni2+ ions from aqueous solution using date pits in the batch adsorption experiments. The results have shown that the Al-zahdi Iraqi date pits demonstrated more efficient at certain values of operating conditions of adsorbent doses of 0.12 g/ml of aqueous solution, adsorption time 72 h, pH solution 5.5 ±0.2, shaking speed 300 rpm, and smallest adsorbent particle size needed for removal of metals. At the same time the particle size of date pits has a little effect on the adsorption at low initial concentration of heavy metals. The adsorption of metals increases with increasing the initial of metal concentration while above the 85 ppm, the removal efficiency was decreased. The phenomenon of adsorption of heavy metals on to Al-Zahdi Iraqi Date pits is exothermic process. The maximum adsorption capacity according to the Langmuir equation was 0.21, 0.149, and 0.132 mmol/g for Cu2+, Zn2+, and Ni2+ respectively. The adsorption equilibrium was well described by the Freundlich model. The results of Freundlich constants indicated that the adsorption capacity and adsorption intensity of Copper is larger than the Zinc and Nickel. The intraparticle diffusion was involved is this process but it is not the controlling step. The results of this study may inspire to find the optimal operating conditions for adsorption and develop that with large-scale production to clean the polluted water with heavy metals.